Average Packet Transfer Delay Performance of an Enhanced CSMA/CD based Single Channel Fast Ethernet Optical LAN - Kabir, Shamima; M.K, Abdullah; Khatun, Sabira; M.A, Mahdi (Malaysian Journal of Science, 2007)
CSMA/CD based Ethernet does not guarantee delay bound and behaves poorly under heavy load conditions because of excessive collisions and backoff algorithm. It is not suitable for supporting real-time multimedia traffic. This paper presents an enhanced CSMA/CD to improve average packet transfer delay by reducing collisions. Here, each node has a finite buffer capacity that helps to reduce collisions. To guarantee a bounded delay for multimedia applications, the maximum retransmission attempt and backoff limit are reduced from 16 to 10 and from 10 to 8 respectively. Average packet transfer delay based on proposed CSMA/CD is evaluated against several design parameters i.e. number of nodes, bus length and offered load. The delay results show significant improvement. Percentage of collisions is reduced to less than 3% and thereby average packet transfer delay is reduced to less than 2 ms compared to conventional CSMA/CD.